Pemberdayaan Anggota Kelompok Tani Melalui Penerapan Tumpangsari Budidaya Ubi Jalar dengan Tanaman Jagung Manis di Kecamatan Cibeber Kabupaten Cianjur, Jawa Barat - Nurul Hasanah; Kusmiyati Kusmiyati; Dwiwanti Sulistyowati (Jurnal Penyuluhan Pertanian, 2020)
Sweet potato plants are generally planted monoculture by farmers, so that the cultivation activities in one season only focus on one commodity and no other mixed commodities. The possibility that occurs when implementing a monoculture cropping system is a failure to harvest or small production results if the plant is attacked by pests or diseases, also less optimal use of the land used. One effort to overcome this problem is the intercropping system. The purpose of this study is to describe the level of empowerment of farmer group members through the application of sweet potato cultivation intercropping with sweet corn plants, analyzing the influential factors and strategies to increase the empowerment of farmer group members through the adoption of sweet potato cultivation intercropping with sweet corn plants. The population of this study was 145 people and 61 samples were taken. Data analysis methods used are descriptive statistical analysis, multiple linear regression analysis, and Kendall's W. analysis. The results of the study show that the level of empowerment of farmer group members in the three research object villages is in the high category of 38 people or (62.30%) of the total overall respondent. The factors that influence the empowerment of farmer group members through the implementation of intercropping are external factors in extension activities. The strategy to increase the empowerment of farmer group members through the implementation of intercropping by carrying out counseling containing material about intercropping and sweet potato cultivation systems.